Asthma, rhinitis and eczema symptoms in Quito, Ecuador: a comparative cross-sectional study 16 years after ISAAC - Luis Garcia-Marcos; Alejandro Rodriguez; Angelita Cabrera; Cèsar Picado (BMJ Open Respiratory Research)
Background In 2003, the International Study of Asthma and Allergies in Childhood (ISAAC) estimated the prevalence of asthma, rhinitis and eczema symptoms in Quito, Ecuador. Since then, no update of this study has been done in the last years. This study examined changes in the prevalence of asthma–rhinitis–eczema symptoms over a 16 years period in Quito and explored possible risk factors.Methods We conducted a comparative cross-sectional study in an adolescent population following the Global Asthma Network (GAN) methodology. A written questionnaire was used to explore symptoms of asthma–rhinitis–eczema. We calculated the prevalence and 95% CIs for each of the symptoms and compared them with the ISAAC results. We conducted bivariate and multivariate analysis using logistic regression to identify possible risk factors for recent wheeze, rhinitis and eczema.Results A total of 2380 adolescents aged between 13 and 14 years were evaluated. The prevalence of doctor diagnosis for asthma, rhinitis and eczema was 3.4%, 8.5% and 2.2%, respectively. Compared with ISAAC results, we found a lower prevalence of wheeze and eczema symptoms: wheeze ever (37.6% vs 12.7%), recent wheeze (17.8% vs 6.5%), asthma ever (6.9% vs 4.6%), recent rush (22.4% vs 13.9%) and eczema ever (11.7% vs 3.6%). The prevalence of rhinitis symptoms in the GAN study was higher than the ISAAC results: nose symptoms in the past 12 months (36.6% vs 45.8%) and nose and eye symptoms in the past 12 months (23.1% vs 27.9). Significant associations were observed between symptoms of asthma–rhinitis–eczema and sex, race/ethnicity, smoking habit, physical exercise and sedentary activities.Conclusions In the last two decades, the prevalence of asthma and eczema symptoms in adolescent population in the city of Quito has significantly declined; however, the prevalence of rhinitis symptoms has increased. The reduction in asthma symptoms could be related to better managing the disease and changes in local environmental risk factors in the last years. Further studies must be conducted in the country to evaluate the change in trends in asthma and other related allergic diseases.